Penyuluhan Potensi Kegiatan Wirausaha Desa Ramah Lingkungan di Kabupaten Manokwari - Ketysia Imelda Tewernusa; Maria Magdalena Semet; Yuyun Puji Rahayu (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Dissemination of information to villages, especially in remote, outermost and smallest areas about strategic issues of welfare improvement that can be developed has not been widely implemented. By taking the example of a village located on the outskirts of the city, the purpose of outreach activities about the potential for entrepreneurial activities in the village is to disseminate knowledge and information as well as provide motivation to the population, most of whom only work as subsistence farmers. The result of this activity is an increase in the knowledge of the extension participants in terms of carrying out activities that have economic value using natural resources that are already available in the village. Thus, residents can create additional income opportunities without leaving their main activities as farmers.